THE CREATIVE BIOGRAPHY OF MARIA SHYMANOVSKA IN THE CONTEXT OF THE PROBLEM OF IDENTITY - Janyshyn-Pryimenko, Mariia (Ukrainian Cultural Studies, 2023)
The article examines the problem of the artists’ identity at the beginning of the 19th century through the prism of the Maria Shymanovska’s creative personality. The analysis of the historical and cultural realities of the time made it possible to determine the main factors that influenced the formation of identity. These are geography, religion, social status and gender. It was found that for Maria Szymanowska, Warsaw always remained the central city through which her self-determination took place, even after moving to St. Peregburg in 1828. There was a problem of coherence between the national and religious identities of the artist. Szymanowska was Polish at the level of "I speak the language, I dress," but she was a frankist at the level of "whom I pray to, what books I read, who I believe in," which makes her identity portrait more complex. The composer sought to create a positive image in the aristocratic society and position herself as part of it, thus increasing the social status given to her at birth – petty bourgeoisie, the daughter of a brewer. She did this with acquaintances, a suitable social circle, portraits, clothes, etc. Also, the artist bravely overcame the boundaries of established behavioral models for women. Maria Shymanovska divorced and supported herself and three children from the marriage – artistic and compositional activities were the main source of her income. Through the prism of periodicals of the day, she appears as one of the first women who dares to compete with men on a professional level. Various aspects of Maria Szymanovska’s creative biography are intricately intertwined and clash with each other at different levels: Szymanovska is a Polish, but primarily defends the interests of a narrow group of frankists; the artist belongs to the bourgeoisie, but it is important for her to position herself as an aristocrat; she is a woman, however, first of all, she chooses her right to creative and professional realization. The comparison of typical life strategies, which provided for the mentioned factors of identity formation, with the life and creative decisions of Maria Shymanovska, made it possible to outline the specifics of the artist’s identity portrait. By overcoming the established identity stereotypes of the time, Maria Shymanovska appears as an extraordinary person who is able to shape new life strategies